Measure of nonhyperconvexity and fixed-point theorems. (30th January 2003) - Bugajewski, Dariusz; Espínola, Rafael
Abstract : The aim of this paper is to work with the measure of nonhyperconvexity in a similar way as J. Cano (1990) does with the index of nonconvexity. We apply this measure to obtain different extensions of the famous Schauder fixed-point theorem in hyperconvex spaces.